PENGARUH FEE AUDIT, ROTASI AUDITOR, DAN REPUTASI KAP TERHADAP KUALITAS AUDIT - Indah Yunita Permatasari; Christina Dwi Astuti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
The purpose of this research was to analyze the influence of audit fee, audit switching and audit firm reputation on audit quality. The proxy of audit quality is using discretionary accrual Modified Jones model (1994). Data in the current research were secondary data obtained from the financial statements of property, real estate and construction companies listed on the Indonesia Stock Exchange during 2014-2016. Fourty-four (n = 44) companies was selected using the purposive sampling method as the sample of the current study (N=132). Data was analyze during the multiple regression analysis. The resulted showed that audit fee, audit switching and audit firm reputation has positive significant effects on audit quality.